DAMPAK EXPERIENTIAL MARKETING TERHADAP MINAT BELI PRODUK IKEA - Rosady, Nurvica; Suharyanti, Suharyanti; Anitawati, M. Th. (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2019)
In an era of increasingly fierce competition coupled with the emergence of various kinds of information sources, producers must build good marketing communication to promote their products so consumers can know the quality and the uniqueness of the product. One of the promotional tools is experiential marketing, which has five types of experience, Sense, Feel, Think, Act, and Relate called SEMs (Strategic Experience Modules). This study aims to look at the effect of experiential marketing on the purchase intention of IKEA products. The population is consumers who have visited the IKEA store and are over 22 years old. A sample of 100 people obtained by purposive sampling. By using multiple regression analysis, the results showed that Sense and Act significantly influence purchase intention, and the influence of Sense is more significant than the Act. However, independent variables all together affect purchase intention. The ability of independent variables to explain variations in purchase intention is meager. Therefore other additional independent variables are needed in further research. To cite this article (7th APA style): Rosady, N., Suharyanti, & Anitawati, M. Th. (2019). Dampak Experiential Marketing terhadap Minat Beli Produk IKEA [The Impact of Experiential Marketing on Purchase Intention of IKEA Product]. Journal Communication Spectrum, 9(2), 176-188. http://dx.doi.org/10.36782/jcs.v9i2.1986